STRATEGI CV. GAHARU PLAZA INDONESIA DALAM MEMASARKAN PRODUK TURUNAN GAHARU DI PASAR MALAYSIA - Bella Chairati Fatimah Putri Putri; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain the strategy of CV. Gaharu Plaza Indonesia is marketing gaharu derivative products in the Malaysian market. Opportunities CV. Gaharu Plaza Indonesia to market gaharu derivative products in the Malaysian market has been further facilitated by the cooperation between Indonesia and Malaysia which was formed in the Malaysia-Indonesia Social Economic Cooperation (SOSEK MALINDO) and Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) forums. The research data is obtained from books, journals, official documents and websites that support the hypothesis. The author use liberalis approach and group analysis. And the theory used in this study is the theory of international trade. The method used is a qualitative research method. This analysis is based on data obtained from literature studies and field studies by conducting interviews directly with informants who are considered capable of providing information regarding the problem under study. The results of the research show that the CV strategy. Gaharu Plaza Indonesia in marketing gaharu derivative products in the Malaysian market is by increasing excellence through product development, promotion, competitive prices, clear distribution systems and utilizing facilities provided by the Indonesian Government in promoting products abroad.Keywords: Agarwood Derivative Products, Market, SOSEK MALINDO, IMT-GT.